Current and future medical treatments for patients with acromegaly. (12th August 2016) - Maffezzoni, Filippo; Formenti, Anna Maria; Mazziotti, Gherardo; Frara, Stefano; Giustina, Andrea
ABSTRACT: Introduction : Acromegaly is a relatively rare condition of growth hormone (GH) excess associated with significant morbidity and, when left untreated, high mortality. Therapy for acromegaly is targeted at decreasing GH and insulin-like growth hormone 1 levels, ameliorating patients' symptoms and decreasing any local compressive effects of the pituitary adenoma. The therapeutic options for acromegaly include surgery, medical therapies (such as dopamine agonists, somatostatin receptor ligands and the GH receptor antagonist pegvisomant) and radiotherapy. However, despite all these treatments option, approximately 50% of patients are not adequately controlled. Areas covered : In this paper, the authors discuss: 1) efficacy and safety of current medical therapy 2) the efficacy and safety of the new multireceptor-targeted somatostatin ligand pasireotide 3) medical treatments currently under clinical investigation (oral octreotide, ITF2984, ATL1103), and 4) preliminary data on the use of new injectable and transdermal/transmucosal formulations of octreotide. Expert opinion : This expert opinion supports the need for new therapeutic agents and modalities for patients with acromegaly.